Implementing the 'Prevent Duty' in England: the semiotisation of discourse and practice in further education. Issue 4 (3rd July 2020) - Beighton, Christian; Revell, Lynn
ABSTRACT: This paper examines the implementation of the Prevent Duty to actively promote fundamental British values in English Further Education (FE). After critically reviewing the history of Prevent and the 2015 Duty to identify evidence of radicalisation in FE, data from interviews of strategic decision-makers in two distinct cases is analysed. The identification, interpretation and recirculation of verbal, graphic and behavioural signs of radicalisation is highlighted. Pinpointing a 'semiotisation' of the Prevent agenda, practical and conceptual implications are discussed. First, we identify a practical preoccupation with signs, specific beliefs about how they work, and how decision-makers deal with them. Second, we divide these beliefs conceptually into univocal and polyvocal semiotisation, referring to the degree to which signs are understood as unequivocal indicators of meaning. We underline significant variations in practice in this context and implications which, we argue, link practice and research to inform the fields of (edu)semiotics and policy enactment.